Pengembangan Sistem Pengajaran Flora dan Fauna Secara Bilingual Berbasis Web - Dwi Sakethi; Irwan Adi Pribadi; Citra Marshella (Universitas Lampung, 2014)
Science is the study of nature and its surroundings, including the flora and fauna. Flora are plants that live in a particular habitat or area, while the fauna are animals that live in a particular habitat or area. At the elementary school level, students learn about the introduction of flora and fauna such as the characteristics, environmental habitat, breeding, and food type. During this time, elementary school students are introduced to flora and fauna only through book. In this research, the web-based bilingual teaching system of flora and fauna using Indonesian and English was developed for elementary school students. The system is built using waterfall methods with MySQL database and the PHP programming language. The system was created with the aim to help students get to know the flora and fauna in the surrounding environment and can increase the student’s knowledge of English.Keywords: fauna, flora, system.